Tingkat Pengetahuan dan Sikap Ibu Hamil Trimester III tentang Metode Kontrasepsi Intra Uterine Device Pasca Persalinan - Sudani, Ni Wayan; Suindri, Ni Nyoman; Senjaya, Asep Arifin (JURNAL KEBIDANAN, 2025)
Written in one paragraph The government establishes family planning policies through the implementation of family planning programs to create a balanced population growth and quality families, in accordance with Law Number 52 of 2009 concerning Population Development and Family Development. The low number of post-placental IUD acceptors is due to a lack of knowledge about post-placental IUDs. This research is a descriptive study with a quantitative approach used. The research location and data collection in this study was carried out at the Tampaksiring I Community Health Center, Jalan DR. IR. Soekaeno, Tampaksiring, Gianyar Regency. The research results showed that most of the respondents had multigravida parity status, 71.7%. Therewere 48 respondents (90.6%) who had a positive attitude about postpartum IUD contraception. All respondents had been exposed to information about postpartum IUDs, the majority of respondents had good knowledge about postpartum IUDs, namely 50 respondents (94.3%). most of the information came from electronic media as much as 69.8%. This shows that of the 53 respondents studied, there were 44 respondents (83%) who had secondary education, and only 9 respondents (17%) had tertiary education. Conclusion: Education is closely related to knowledge, the higher a person's level of education is expected to be easier to grasp the knowledge conveyed. Knowledge of third trimester pregnant women regarding postpartum intrauterine device contraceptive methods is more likely to be in the good category. The attitudes of third trimester pregnant women regarding intrauterine device contraceptive methods postpartum people have more positive attitude categories